Lucian and Tatian: about the Afterlife and the Last Judgment (Circe de clásicos y modernos, 2018)
The framework and the characters of Lucian’s descriptions of the afterlife, focusing in particular on the decisions of Rhadamanthys as a judge of human beings, show a kind of morality which can be analyzed both from the perspective of traditional Graeco-Roman stand-ards and from that of the new religious contexts of the Roman Empire. Christian apologists, on the other hand, like Tatian in Oratio ad Graecos, insist on distinguishing clearly between the judgment of Rhadamanthys and that of God himself. Both views of the afterlife are influenced by Greek myth and by Plato’s manipulation of it. The loss of the ancient function of myth among the pagans and the real presence of Christian issues regarding the afterlife may have caused a writer like Lucian to reflect on the real sense of the afterlife.
Keywords: Afterlife; Rhadamanthys; Lucian; Tatian; Religion